Pengaruh Lingkungan Kerja, Kepuasan Kerja, dan Beban Kerja Terhadap Kinerja Pegawai - Nurhandayani, Annisa (EKONOMI DAN BISNIS DIGITAL, 2024)
This study aims to determine and analyze the influence of the work environment, job satisfaction, and workload on the performance of employees of the Aceh Tamiang Regency Public Works and Public Housing Office, totaling 81 people. This study uses validity and reliability analysis for a questionnaire test. Then a regression analysis was carried out to see how much the correlation was between each independent variable and the dependent variable using statistical tools (SPSS). From the research it was obtained that partially the work environment, job satisfaction and workload do not have a significant effect on the performance of employees of the Public Works and Public Housing Office of Aceh Tamiang Regency, but simultaneously work environment, job satisfaction and workload have a significant effect on the performance of employees of the Public Works and Public Housing Office of Aceh Tamiang Regency.